2018
DOI: 10.1371/journal.pmed.1002508
|View full text |Cite
|
Sign up to set email alerts
|

The 2014–2015 Ebola virus disease outbreak and primary healthcare delivery in Liberia: Time-series analyses for 2010–2016

Abstract: BackgroundThe aim of this study is to estimate the immediate and lasting effects of the 2014–2015 Ebola virus disease (EVD) outbreak on public-sector primary healthcare delivery in Liberia using 7 years of comprehensive routine health information system data.Methods and findingsWe analyzed 10 key primary healthcare indicators before, during, and after the EVD outbreak using 31,836 facility-month service outputs from 1 January 2010 to 31 December 2016 across a census of 379 public-sector health facilities in Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 35 publications
4
122
0
Order By: Relevance
“…Liberia is only 12 years removed from 14 years of civil conflict which devastated an already weak health system. In addition, Liberia recently emerged from the worst EVD epidemic known to date . Our findings that an 76% reduction in LTFU rates can be obtained over a relatively short time period immediately after the EVD outbreak is a testament to the strength of CHW interventions, and their potential for positive impacts on TB care and treatment.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Liberia is only 12 years removed from 14 years of civil conflict which devastated an already weak health system. In addition, Liberia recently emerged from the worst EVD epidemic known to date . Our findings that an 76% reduction in LTFU rates can be obtained over a relatively short time period immediately after the EVD outbreak is a testament to the strength of CHW interventions, and their potential for positive impacts on TB care and treatment.…”
Section: Discussionmentioning
confidence: 75%
“…There is an estimated 16% national treatment default rate . The 2014‐2015 Ebola virus disease (EVD) outbreak exacerbated the situation , causing an estimated 11 533 additional TB‐related deaths in Liberia (compared with 4769 deaths directly from EVD) as modelled using decision trees by Parpia et al . .…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies found large discrepancies between RHIS data and an estimated disease burden in populations or highlighted the lack of service provision. A few studies also used RHIS data to describe speci c programs [60][61][62][63][64] , conduct impact evaluations (non-programmatic) [65][66][67][68] , and estimate costs 69,70 .…”
Section: Resultsmentioning
confidence: 99%
“…Time series analysis using RHIS data was most often applied to evaluate programs and identify disease epidemiology, with one study assessing the impact of an infectious disease outbreak on primary health service utilization 73 . Studies analyzed indicators using large quantities of monthly or yearly data to estimate change (range of time units: 5 -168).…”
Section: Time Series Analysismentioning
confidence: 99%
See 1 more Smart Citation